2020
DOI: 10.1111/gcb.15450
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying thermal exposure for migratory riverine species: Phenology of Chinook salmon populations predicts thermal stress

Abstract: Migratory species are particularly vulnerable to climate change because habitat throughout their entire migration cycle must be suitable for the species to persist. For migratory species in rivers, predicting climate change impacts is especially difficult because there is a lack of spatially continuous and seasonally varying stream temperature data, habitat conditions can vary for an individual throughout its life cycle, and vulnerability can vary by life stage and season. To predict thermal impacts on migrato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(63 citation statements)
references
References 81 publications
2
61
0
Order By: Relevance
“…2008; see also the discussion by FitzGerald et al. 2020). Overall, the scope for local adaptation to the prevailing thermal regime seems greater for the spawning stage than for the holding stage.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…2008; see also the discussion by FitzGerald et al. 2020). Overall, the scope for local adaptation to the prevailing thermal regime seems greater for the spawning stage than for the holding stage.…”
Section: Discussionmentioning
confidence: 89%
“…However, FitzGerald et al. (2020) recently reviewed accounts of spawn timing throughout California and found that spring‐run Chinook Salmon may spawn as early as August or as late as December. Thompson et al.…”
Section: Discussionmentioning
confidence: 99%
“…Diadromous fish populations such as Atlantic salmon are in drastic decline worldwide due to the effects of global change on both freshwater and marine environments [ 78 , 79 ]. Changes in one life stage can propagate throughout the life cycle and affect subsequent life stages or accumulate over several generations [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…For aquatic ectotherms, temperature is the primary abiotic factor that controls biophysical, biochemical and bioenergetic processes ( Fry, 1971 ), thus influencing spatial distributions ( Fourcade et al, 2018 ), physiological rates, daily and long-term survival and evolutionary trajectory ( Brannon et al, 2004 ). Seasonal patterns in temperature have resulted in corresponding patterns in life history, phenology and spatial distribution for aquatic populations, such that a geographically widespread species may consist of multiple populations with unique thermal environments and thermal adaptations ( Chen et al, 2013 ; Eliason et al, 2011 ; FitzGerald et al, 2021 ; Flitcroft et al, 2016 ; Nadeau et al, 2017 ; Quinn, 2018 ; Stitt et al, 2014 ; Zillig et al, 2021 ). Sudden shifts in the long-term thermal average can induce conditions for which a population has not experienced.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of the water, timing of release, duration of release, amount of water and discharge rate are constantly debated because the thermal requirements for one life stage or species may be harmful to another (e.g. Zarri et al, 2019 ), interspecific populations may exhibit different adaptations ( Eliason et al, 2011 ; Zillig et al, 2021 ) and thermally suitable habitat may vary spatially and temporally ( Armstrong et al, 2021 ; FitzGerald et al, 2021 ). These conditional effects are not well-studied due to their complexity, indicating a need for a spatially and temporally explicit comparative model that can estimate population-specific thermal impacts on sympatric and successive life stages ( Crozier et al, 2017 ; Crozier et al, 2021 ; Snyder et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%